2021
DOI: 10.1055/s-0041-1726046
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Turbinate Reduction during Rhinoplasty: Is There Any Effect on Rhinitis Symptoms?

Abstract: Introduction Inferior turbinate surgery is often performed concomitantly with rhinoseptoplasty. As inferior turbinates play a major role in allergic rhinitis, it seems reasonable to suggest that inferior turbinate surgery reduces allergy. Objective To assess the impact of nasal turbinate surgery on non-obstructive allergic symptoms (nasal discharge, sneezing, pruritus, and allergic conjunctivitis) and on the use of allergic medication in patients with allergic rhinitis undergoing rhinoseptoplasty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Recent studies 50,69 have shown that NSR + BIT and NSR have no statistical difference in the improvement of nonobstructive allergic symptoms, which was consistent with our results. But after a network meta-analysis, we found that its ranking was higher than NSR.…”
Section: Response Rate In Allergic Rhinitis Combined With Chronic Rhi...supporting
confidence: 93%
“…Recent studies 50,69 have shown that NSR + BIT and NSR have no statistical difference in the improvement of nonobstructive allergic symptoms, which was consistent with our results. But after a network meta-analysis, we found that its ranking was higher than NSR.…”
Section: Response Rate In Allergic Rhinitis Combined With Chronic Rhi...supporting
confidence: 93%
“…It is important to note that the key players driving the severity of AR symptoms are both allergic mucosa inflammation in the inferior turbinates as well as increased turbinate size. 23 As such, symptom relief may require these 2 factors contributing to refractory nasal obstruction to be targeted. Currently, patients with AR are often treated by only allergist or ENT surgeons, with minimal overlap, and therefore will be directed to AIT or ITR preferentially.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the key players driving the severity of AR symptoms are both allergic mucosa inflammation in the inferior turbinates as well as increased turbinate size. 23 As such, symptom relief may require these 2 factors contributing to refractory nasal obstruction to be targeted.…”
Section: Discussionmentioning
confidence: 99%